BIOLOGICAL ASSOCIATIONS BETWEEN RESISTIN, ADIPONECTIN, VISFATIN AND GHRELIN HORMONES WITH SOME COAGULATION MARKERS - Hayder, Zh. Sh.; Kareem, Z. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to investigate the biological association between resistin, adiponectin, visfatin and ghrelin hormones with some coagulation markers. The study included 130 patient and 42 healthy subjects. Serum resistin, adiponectin, visfatin, ghrelin and some other hematological and biochemical parameters were estimated. Statistical analysis showed that altered resistin, adiponectin, visfatin, and ghrelin levels were significantly and directly or indirectly through insulin resistance (IR) associated with clotting markers. From the main studied levels of adipokines, ghrelin, and clotting parameters, the study indicated high levels of serum resistin, adiponectin, visfatin and ghrelin hormones in NIDDM, ESRD, NIDDM+ESRD patients. Also, altered platelets (PLT), mean platelet volume (MPV), prothrombin time (PT), activated partial prothrombin time (aPPT), plasminogen activator inhibitor- 1 (PAI-1), and fibrinogen1 were observed. The studied adipocytokines and ghrelin concentration was correlated directly and indirectly through IR with the studied clotting parameters.